Primer Informe del Virus de la Papa Y en Calibrachoa Ornamental en Argentina - Tombion, Leticia (2019)
The identification of the calibrachoa-infecting PVY strain is vital for resistant-cultivar selection, and therefore it should be addressed in future studies. To our knowledge, this is the first report of PVY as a pathogen of Calibrachoa in Argentina.